The Long-Term Outcomes of Ablation With Vein of Marshall Ethanol Infusion vs. Ablation Alone in Patients With Atrial Fibrillation: A Meta-Analysis - Feng Li; Jin-Yu Sun; Li-Da Wu; Lei Zhang; Qiang Qu; Chao Wang; Ling-Ling Qian; Ru-Xing Wang (Frontiers in Cardiovascular Medicine, 2022)
BackgroundThe long-term outcomes of ablation with vein of Marshall ethanol infusion (VOM-ABL) compared with ablation alone in patients with atrial fibrillation (AF) remains elusive. We aimed to explore whether VOM-ABL showed better long-term benefits and screen the potential determinants of outcome impact of VOM-ABL procedure.MethodsPubMed, Cochrane Library, Web of Science, and Embase were searched up to 1st September 2021. Studies comparing the long-term (one-year or longer) outcomes between VOM-ABL and ablation alone were included. Subgroup analysis identified potential determinants for VOM-ABL procedure.ResultsCompared with ablation alone, VOM-ABL was associated with a significantly higher rate of long-term freedom from AF/AT (risk ratio [RR], 1.28; 95% confidence interval [CI], 1.12–1.47; p = 0.00) and successful mitral isthmus (MI) block (RR, 1.52; 95% CI, 1.16–1.99; p = 0.00), whereas, there was no significant difference in pericardial effusion, stroke/transient ischemic attack (TIA), and all-cause death. Subgroup analysis identified two significant treatment-covariate interactions: one was ablation strategy subgroup (pulmonary vein isolation plus linear and/or substrate ablation [PVI+]; RR, 1.41; 95% CI, 1.27–1.56 vs. PVI; RR, 1.05; 95% CI, 0.92–1.19, p = 0.00 for interaction) for freedom from AF/AT, while the other was VOM-ABL group sample size subgroup (≥ 100; RR, 1.98; 95% CI, 1.24–3.17 vs. <100; RR, 1.20; 95% CI, 1.10–1.30, p = 0.04 for interaction) for MI block.ConclusionsThis meta-analysis demonstrates that VOM-ABL has superior efficacy and comparable safety over ablation alone in AF patients with long-term follow-up. Moreover, PVI+ and VOM-ABL group sample size ≥ 100 may be associated with a great impact on freedom from AF/AT and MI block, respectively.